Assessing the Competency and Acceptability of Community Health Worker Provision of Standard Days Method® in Family Planning Services in Gisagara District, Rwanda. Issue 2 (21st May 2018) - VanEnk, Lauren; Shelus, Victoria; Mugeni, Catherine; Mukabatsinda, Marie; Cachan, Jeannette
Abstract: This study assesses the competency and acceptability of community‐based provision of Standard Days Method ® (SDM) to first‐time users in Rwanda. The national strategy equips community health workers (CHWs) to resupply pills, injectables and condoms to existing clients. With the aim of expanding access, SDM provision to first‐time users was added to the method mix in Gisagara district and assessed with a 12 month prospective, mixed methods study. Thirty percent of SDM clients had never used a method of family planning and 58 percent had not been using a method for at least three months. Eighty‐seven percent of CHWs correctly screened clients to use SDM and 92 percent accurately explained how to use CycleBeads to prevent pregnancy. After being counseled by the CHWs, 89 percent of clients reported knowledge of all key steps required in using SDM to prevent pregnancy. Nearly all SDM clients (99 percent) believed that CHWs were able to counsel them adequately. These results suggest that CHWs were able to offer SDM as part of their family planning responsibilities, and the study adds to the evidence on the role of CHWs in expanding contraceptive access and choice.